Eltrombopag can promote platelet implantation after allogeneic hematopoietic stem cell transplantation as safely and similarly to thrombopoietin - Li, Yahan; Kong, Fansheng; Bai, Guanchen; Jiang, Yujie; Zhang, Wenlu; Sun, Xue; Sui, Xiaohui; Li, Ying; Ding, Mei; Yuan, Dai; Wang, Xin; Fang, Xiaosheng (Frontiers in Immunology, 2024)
Eltrombopag has demonstrated efficacy in treating low platelet (PLT) levels, but it remains unclear whether eltrombopag can promote PLT engraftment after hematopoietic stem cell transplantation (HSCT). Forty-one HSCT patients received eltrombopag 50 mg/d from +1 day until PLT >50 × 10 9 /L or 1 month after HSCT. Fifty-one patients in the same period received thrombopoietin (TPO) to promote PLT graft after HSCT and served as a control group. A total of 51 patients who applied TPO during the same period were treated as a control. In the eltrombopag group, the median time to white blood cells (WBC) graft was 12 days (range, 10-17 days) and the PLT graft was 15 days (range, 10-30 days), whereas for the patients in the TPO group, the median time to WBC and PLT graft was 12 days (range, 9-23 days) and 15.5 days (range, 9-41 days), respectively. In the first month after HSCT, the median WBC count in the eltrombopag group was 4.41 × 10 9 /L (range, 0.87-40.01 × 10 9 /L) and the median PLT was 89x10 9 /L (range, 30-401 × 10 9 /L); the median WBC and PLT \counts in the TPO group were 4.65 × 10 9 /L (range, 0.99-23.63 × 10 9 /L) and 86 × 10 9 /L (range, 5-512 × 10 9 /L), respectively. Patients in the TPO or eltrombopag group did not experience serious side effects after drug administration, and the difference in side effects on liver and kidney function between the two groups was not statistically significant. Eltrombopag is safe and similarly promotes platelet engraftment to thrombopoietin after allogeneic HSCT.